The Impact Of Service Quality And Corporate Image On Customer Loyalty - A Study On Perodua Service Centre - MOHD NASIR, ASMA AZURA (2004)
In order to meet the AFTA (Asean Free Trade Area) challenges in 2005, local automobile industries especially Perodua had prepared its strategy to move forward to compete in the globalization market. Perodua has set its target to maintain the market share, reduce cost and increase Customer Satisfaction Index (CSI) especially in Perodua Service Centre with the slogan “Kearah 333”.